Pengaruh Game Online terhadap Kualitas Tidur pada Anak Usia Sekolah di SD N 2 Tambaknegara - Tastrya Nur Yunita; Ikit Netra Wirakhmi; Wasis Eko Kurniawan (Universitas Harapan Bangsa, 2021)
Online games are games that are played by multiplayer over the internet. Usually provided as an addition to the services of online service providers or can be accessed directly from companies that specialize in providing games in playing online games, there are two important devices that must be owned, namely a set of computers with marked specification with connection to the internet. This study aims to determine the effect of online games on sleep quality in school-age children at SD N 2 Tambaknegara. This type of research is an analytic survey with a cross sectional approach, a population of 44 children and a sample of 30 respondents using the non probability sampling technique with metode accidental sampling. The research instrument used a questionnaire using a questionnaire sheet. Data analysis used Spearman Rank correlation test. The results showed that the habit of playing online games was mostly in the always category as many as 16 respondents (53.3%) and the few in the never category were 2 respondents (6.7%), while for the quality of sleep the most was in the quality category. 18 respondents (60%) bad sleep and a few in the good sleep quality category as many as 12 respondents (40%) and for the influence of online gaming habits on sleep quality, the correlation coefficient test results were -0.870 with p-value <0.001 . The conclusion of this study is that there is a relationship between online gaming variables and sleep quality at SD N 2 Tambaknegara but not in the same direction, so that there is an influence of online games on sleep quality between schools and health workers to provide counseling about the impact of playing online games on sleep quality to students.